Lexical Phonology and Nonconcatenative Morphology in the History of Chaha - McCarthy, John (Revue québécoise de linguistique)

(untitled) (Université du Québec à Montréal, 1986)
AbstractA problem in the historical phonology of the Ethiopian Semitic language Chaha is examined from the point of view of lexical phonology and the theory of nonconcatenative morphology. It is argued that systematic exceptions to the devoicing of geminate obstruents are derived from the principle of Geminate Inalterability interacting with Tier Conflation and the Strict Cycle.